Persecutory ideation and a history of cannabis use. - Freeman, D; Morrison, P; Murray, R; Evans, N; Lister, R; Dunn, G (2013)
BACKGROUND: Cannabis use is associated with the occurrence of psychotic experiences. However there are multiple distinct psychotic experiences, each likely to occur as quantitative traits in the general population. In this study we tested for an association of cannabis use with a dimensional assessment of persecutory ideation. METHOD: A total of 1714 individuals from the general population completed a dimensional measure of current persecutory ideation and reported on whether they had ever taken cannabis. RESULTS: Of all participants, 648 (38%) reported a history of cannabis use. These individuals reported significantly higher current levels of persecutory ideation. The amount of variance in paranoia scores explained was low. Individuals with a history of cannabis use had almost twice the odds of reporting any paranoid ideation in the past month compared with individuals who had never taken cannabis. CONCLUSIONS: Using a state of the art assessment, the study adds to findings of an association of persecutory ideation with cannabis use.